Sustained release of cathepsin D/cathepsin K from injectable hydrogel microspheres in anti-photoaging - Wenyi Hou; Zhaoyi Lin; Xinling Chen; Yu Sun; Yao Lin; Mengran Peng; Feng Zhou; Huamin Jiang; Yan Li; Yue Zheng (Materials Today Bio)
There have been various interventions for photoaging skin, such as retinoic acid treatment and laser therapy. However, more precise, secure, and effective technologies and materials were still need to be explored. Cathepsin D (CTSD) repairs the epidermal barrier in chronic photodamaged skin through increasing TGase-1 expression and activity. Cathepsin K (CTSK) affects the metabolism of skin elastic fibers. Therefore, gelatin/alginate composite hydrogel microspheres loaded with CTSD or CTSK were fabricated. The microspheres with an average size of 79.8 ± 30.4 μm were stable in PBS (pH 7.4) for 5 days and then disintegrated in vitro. 0.1 mg/mL of microspheres continuously released 12–13 ng/mL CTSD or CTSK for the first three consecutive days. In vivo, the microspheres were almost completed degraded on day 7 after the subcutaneous injection. The biosafety and efficacy of CTSD- and CTSK- microspheres were confirmed in vitro and in vivo. They reduced ROS and inhibited the degradation of skin collagen and elastic fibers by upregulating Nrf2 and downregulating MMP-1 and MMP-3, which reversed photodamage of skin induced by UV. In conclusion, the gelatin/alginate composite microspheres loaded with CTSD or CTSK showed a great potential for chronic photodamaged skin.